Itsy Bitsy Spider…: Infants React with Increased Arousal to Spiders and Snakes - Hoehl, Stefanie; Hellmer, Kahl; Johansson, Maria; Gredebäck, Gustaf (Frontiers in Psychology, 2017)
Attention biases have been reported for ancestral threats like spiders and snakes in infants, children, and adults. However, it is currently unclear whether these stimuli induce increased physiological arousal in infants. Here, 6-month-old infants were presented with pictures of spiders and flowers (Study 1, within-subjects), or snakes and fish (Study 1, within-subjects; Study 2, between-subjects). Infants’ pupillary responses linked to activation of the noradrenergic system were measured. Infants reacted with increased pupillary dilation indicating arousal to spiders and snakes compared with flowers and fish. Results support the notion of an evolved preparedness for developing fear of these ancestral threats.